Tasawuf Lokal Panglima Utar di Kotawaringin Barat, Kalimantan Tengah - Sulaiman Sulaiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2017)
This article explores the thought of a local Sufism, Panglima Utar (Mukhtar bin Abdurrahim), originated from West Kotawaringin, CentralKalimantan. It focuses on the only manuscript written by him. The manuscript gives valuable information about the continuity of his thought and the established teaching of mysticism in Kalimantan since the 17th and 18th century. In this manuscript, he explains the position of a teacher towards sâlik, the form of wirid and dzikir (praying words), the final purpose as well as the teaching about how to understand Allah (ma‘rifah Allâh). The mysticism thoughts have a significant intellectual and spiritual line. The teachings found in Panglima Utar’s manuscript clearly shows that they are on the mainstream of mysticism thoughts in Indonesian archipelago.